Enhancing the Efficiency of Soybean Inoculant for Nodulation under Multi-Environmental Stress Conditions - WONGDEE, JENJIRA (Pol J Microbiol, 2021)
The development of rhizobial inoculants with increased resistance to abiotic stress is critical to mitigating the challenges related to climate change. This study aims at developing a soybean stress-tolerant Bradyrhizobium inoculant to be used under the mixed stress conditions of acidity, high temperature, and drought. Six isolates of Bradyrhizobium with high symbiotic performance on soybean were tested to determine their growth or survival abilities under in vitro conditions. The representative stress-tolerant Bradyrhizobium isolates 184, 188, and 194 were selected to test their ability to promote soybean growth under stress conditions compared to the type strain Bradyrhizobium diazoefficiens USDA110. The plant experiment indicated that isolate 194 performed better in symbiosis with soybean than other Bradyrhizobium strains under stress conditions. Based on the stress tolerance index, soybeans inoculated with isolate 194 showed a high growth performance and significantly better nodulation competition ability than USDA110 under several stress conditions. Interestingly, supplementation of sucrose in the culture medium significantly enhances the survival of the isolate and leads to improved plant biomass under various stress conditions. Analysis of the intra-cellular sugars of isolate 194 supplemented with sucrose showed the accumulation of compatible solutes, such as trehalose and glycerol, that may act as osmoprotectants. This study indicates that inoculation of stress-tolerant Bradyrhizobium together with sucrose supplementation in a medium could enhance bacterial survival and symbiosis efficiency under stress conditions. Although it can be applied for inoculant production, this strategy requires validation of its performance in field conditions before adopting this technology.